Communication between people living with dementia and healthcare practitioners in hospital: developing and evaluating a staff training intervention: the VOICE study - Harwood, Rowan H.; O'Brien, Rebecca; Goldberg, Sarah E.; Allwood, Rebecca; Pilnick, Alison; Beeke, Suzanne; Thomson, Louise; Murray, Megan; Parry, Ruth; Kearney, Fiona; Baxendale, Bryn; Sartain, Kate; et al. (NIHR Journals Library, 2018)
Background 25% of hospital beds are occupied by a person living with dementia. Dementia affects expressive communication and understanding. Healthcare professionals report lack of communication skills training. Objectives To identify teachable effective strategies for communication between healthcare professionals and people living with dementia, and to develop and evaluate a communication skills training course. Design We undertook a systematic literature review, video-recorded 41 encounters between staff and people with dementia, and used conversation analysis to investigate communication problems and solutions. We designed a communication skills training course using co-production and multiple pedagogic approaches. We ran a pilot, followed by six courses for healthcare professionals. We measured knowledge, confidence and communication behaviours before, immediately-and one month-after the course, and undertook interviews with participants and managers. Behaviours were measured using blind-rated videos of simulations. Setting General hospital acute geriatric medical wards; clinical skills centre. Participants We video-recorded 26 people with dementia and 26 professionals. Ten experts in dementia care, education, simulation and communication contributed to intervention development. Six healthcare professionals took part in a pilot course and 45 took part in the training. Results Literature review identified 27 studies, describing ten communication strategies, with modest evidence of effectiveness. Healthcare professional-initiated encounters followed a predictable phase structure. Problems were apparent in requests (with frequent refusals) and in closings. Success was more likely when requests were made directly, with high entitlement (authority to ask), and with lowered contingencies (made to sound less difficult , by minimising the extent or duration of the task, as king patients ‘to try’, offering help, or proposing collaborative action). Closings were more successful if the healthcare professional announced the end of the task, made a specific arrangement, body language matched talk, and through use of ‘closing idioms’. The training course comprised two days, one month apart, using experiential learning, including lectures, video-workshops, small group discussion, simulation (with specially-trained actors) and reflection. We emphasised incorporation of previous expertise, and commitment to person-centred care. 44 participants returned for the second training day; 43 provided complete evaluation data. Knowledge and confidence both increased. Some behaviours, especially relating to closings, were more commonly used after training. The course was highly-rated in interviews, especially the use of simulation, real-life video clips, and interdisciplinary learning. Participants reported that they found the methods useful in practice and were using them a month after the course finished. Limitations Data were from people with moderate to severe dementia, in an acute hospital, during healthcare professional initiated interactions. Analysis was limited to problems and solutions that were likely to be ‘trainable’. Actors required careful preparation to simulate people with dementia. Communication skills training course participants were volunteers, unlikely to be representative of the general workforce, who displayed high levels of baseline knowledge, confidence and skills. Before-and-after evaluations, and qualitative interviews, are prone to bias. Future work Further research should investigate a wider range of health, social care and family carers. Conversation analysis should be used to investigate other aspects of healthcare communication. Conclusions Requests and closings pose particular difficulties for professionals communicating with people with dementia. We identified solutions to these problems and incorporated them into communication skills training, which improved knowledge, confidence and some communication behaviours. Simulation was an effective training modality.